MAZHAB KAUM SANTRI (Implementasi Mazhab Syafiâi di Pondok Pesantren Roudlotuth Tholibin Seputih Surabaya Lampung Tengah) - Aji, Didik Kusno (JURNAL NIZHAM, 2014)
We propose the numerous Madhhab in Islam. One of them is Fiqh Madhhab. Some experts are well-known in Islam, such as: Syafiâi, Hambali, Maliki, and Hanfi. They have various ways to make decision in Islamic laws (Fiqh). Referring to the knowledge, there are the various different ways in worship.Â In addition, we know the several of religious organization, such as: NU, Muhammadiyah, LDII, Persis. Specifically, the religious organization have the own characteristics in the terms of worship and the method of determination of the Islamic law. However, the study of religious has different leader to decide or use Islamic law (Fiqh). Moreover, the Syafiâi.Pesantren is the dominant Islamic boarding school, especially in Indonesia. It has developed more than 2 centuries ago. Even thought, the books that are taught at the Islamic boarding school have been taught since the mid 19th century. There are so many books that can still be learned, even thought those are still taught at the Islamic boarding school. We identify the Islamic boarding school as Madhhab Syafiâi can be easily identified. Finally, we consider that Roudlotuth Tholibin is one of the Islamic boarding schools which adopted by the various Islamic boarding school in Java Island.Â Keywords: Islamic Boarding School (Pesantren), Madhhab, Roudlotuth TholibinÂ